Five-year survival and prognostic factors of osteosarcoma patients in hospital University Sains Malaysia: An eleven year review - Wahidah, Tumijan (2008)
According to World Health Organization (WHO), the estimated annual incidence of osteosarcoma was approximately 4-5 per million peoples, occurring most commonly in the second decade of life. Differences in demography, culture and belief may give different results in survival for Malaysian compared to other countries. OBJECTIVES: The objectives of this study were to determine the five-year survival rate of osteosarcoma patients treated during the study period, to identify the prognostic factors that influence the risk of death of osteosarcoma patients and to establish a model that predicts the survival of osteosarcoma patients. METHODOLOGY: This was a retrospective record review study in which the data was collected from patients' medical records involving 127 patients diagnosed with osteosarcoma treated in HUSM, Kelantan. The recruitment phase of the participants began from lst August 1995 till 31st July 2006 (11 years) and additional follow up period of 12 months, after the recruitment of subjects from 1st August 2006 till 31st July 2007, was included. All patients who fulfilled the criteria were included in the study. Data of osteosarcoma patients were collected from the medical record unit using data collection sheet. Patient's survival status was obtained from the medical record as well as contacting them or by home visit with their consent. The Kaplan- Meier and Cox proportional hazard regression analyses were used in statistical analysis. RESULTS: The overall median survival time for 127 patients with osteosarcoma treated was 47.77 months and the overall five-year survival rate was 48.94% (95% CI: 39.4; 57.8). The significant prognostic factors that influence the death in osteosarcoma were duration of symptoms (adjusted HR. 0.34; 95% CI: 0.19; 0.61,p value=0.023), type of surgery for no cases (adjusted HR. 3.39; 95% CI: 1.85; 6.20,p value<O.OOl) and type of surgery for limb salvage (adjusted HR. 0.14; 95% CI: 0.07; 0.28,p value<0.001). CONCLUSION: Five-year survival rate for osteosarcoma patients treated was acceptably low. The survival rate of osteosarcoma patients treated could be worse if the duration of symptoms were less than 70 days, not having a surgery or had been amputated. However, some important prognostic factors can not be identified in this study.